2022
DOI: 10.3389/fvets.2021.791371
|View full text |Cite
|
Sign up to set email alerts
|

Plant-Derived Polysaccharides Regulated Immune Status, Gut Health and Microbiota of Broilers: A Review

Abstract: In modern intensive breeding system, broilers are exposed to various challenges, such as diet changes and pathological environment, which may cause the increase in the incidence rate and even death. It is necessary to take measures to prevent diseases and maintain optimal health and productivity of broilers. With the forbidden use of antibiotics in animal feed, polysaccharides from plants have attracted much attention owing to their lower toxicity, lower drug resistance, fewer side effects, and broad-spectrum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 73 publications
0
19
0
1
Order By: Relevance
“…It is used in folk medicine as a cure for liver problems and a number of active substances can be found in Antrodia cinnamomea such as polysaccharides. Natural polysaccharides have various functions such as growth promotion, anti-inflammation, maintenance of intestinal mucosal integrity, regulation of intestinal flora (1)(2)(3)(4)(5). It has been reported that health benefits of Antrodia cinnamomea have antioxidants properties due to its polysaccharide, polyphenol and triterpenoid contents (6).…”
Section: Introductionmentioning
confidence: 99%
“…It is used in folk medicine as a cure for liver problems and a number of active substances can be found in Antrodia cinnamomea such as polysaccharides. Natural polysaccharides have various functions such as growth promotion, anti-inflammation, maintenance of intestinal mucosal integrity, regulation of intestinal flora (1)(2)(3)(4)(5). It has been reported that health benefits of Antrodia cinnamomea have antioxidants properties due to its polysaccharide, polyphenol and triterpenoid contents (6).…”
Section: Introductionmentioning
confidence: 99%
“…However, different sources of polysaccharides have different probiotic effects on intestinal microbiota [ 57 ]. Besides, since most plant-derived polysaccharides cannot be digested and degraded in the stomach and small intestine, they are degraded by bacteria in the large intestine and then biotransformed to exert their biological functions [ 58 ]. Furthermore, metabolomic analysis of intestinal contents revealed that Astragalus polysaccharides might influence butyrate metabolism, alanine, aspartate and glutamate metabolism, the conversion of pentose and glucuronide, and D-glutamine and D-glutamate metabolism [ 59 ].…”
Section: Effects Of Plant-derived Polysaccharides On Intestinal Barri...mentioning
confidence: 99%
“…Topical corticosteroids (CS) represent the most commonly prescribed treatment for psoriasis, with dexamethasone (DXM) being one of the recommended treatments. Despite the known efficacy of conventional therapies to decrease signs and symptoms severity, side effects may appear, such as atrophy, development of striae, steroid rosacea and skin bacterial superinfections [ 6 ]. Indeed, novel therapeutical strategies for psoriasis treatment could be represented by alternative approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, novel therapeutical strategies for psoriasis treatment could be represented by alternative approaches. In recent years, naturally derived ingredients such as polysaccharides [ 6 , 7 ], extracts [ 8 ] and essential oils [ 9 ] have gained much attention for their health benefits and tolerability. Tamarind seed gum (Xyloglucan) is a hemicellulose extracted from the seed of the tamarind tree, Tamarindus indica.…”
Section: Introductionmentioning
confidence: 99%